2016
DOI: 10.1186/s12889-016-3662-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perspectives of community health workers from implementing treatment for schistosomiasis using the community directed intervention strategy in an informal settlement in Kisumu City, western Kenya

Abstract: BackgroundThe Community Directed Intervention (CDI) strategy has been used to conduct various health interventions in Africa, including control of Neglected Tropical Diseases (NTDs). Although the CDI approach has shown good results in the control of onchocerciasis and lymphatic filariasis with respect to treatment coverage using community drug distributors, its utility in the control of schistosomiasis among urban poor is yet to be established. Using a longitudinal qualitative study, we explored the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(100 citation statements)
references
References 31 publications
13
87
0
Order By: Relevance
“…Knowledge of disease prevention has been a problem in many endemic countries. Similar to the findings presented here, avoiding contact with infected water was identified by only a small proportion of endemic populations in Kenya, Tanzania, Yemen, and Swaziland (Sady et al, 2015;Mazigo et al, 2010;Odhiambo et al, 2016;Mwanga et al, 2004;Maseko et al, 2016). There was also poor awareness of preventive chemotherapy as a means of disease prevention, which is consistent with the findings in Yemen and Uganda (Sady et al, 2015;Kabatereine et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Knowledge of disease prevention has been a problem in many endemic countries. Similar to the findings presented here, avoiding contact with infected water was identified by only a small proportion of endemic populations in Kenya, Tanzania, Yemen, and Swaziland (Sady et al, 2015;Mazigo et al, 2010;Odhiambo et al, 2016;Mwanga et al, 2004;Maseko et al, 2016). There was also poor awareness of preventive chemotherapy as a means of disease prevention, which is consistent with the findings in Yemen and Uganda (Sady et al, 2015;Kabatereine et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…However, becoming infected with Schistosoma through contact with infected water was not a very common response in surveys conducted in China and Swaziland (Maseko et al, 2016;Liu et al, 2014). Similar to the present study findings, the misconception that the infection can be acquired by the consumption of contaminated water or food was also found to be a common response in African surveys (Acka et al, 2010;Odhiambo et al, 2016;Mwanga et al, 2004;Maseko et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The study finding was consistent with reports by Nzinga et al and Odhiambo et al . Both studies observed that knowledge of the benefits from implementing guidelines was a major motivational factor to utilizing guidelines [15,23]. The study results suggest that new public health initiatives such as guidelines or policy changes will require significant health worker and patient education to increase the chances of successful implementation and improved patient outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…The Ministry of Health and Welfare in India recommended using a mix of media sources that are culture-specific or most effective in the local context, such as print media, posters and newspapers, radio, public announcements, or television. 26 Odhiambo et al 27 reported that more involvement of local community leaders who are respected in the community is also encouraged as they play a pivotal role in sensitising the community and can lead to increased ownership and acceptability of the programmes. Similarly, results of the present study demonstrate that teachers highly recommend the use of media sources (posters, radio, public announcements and television) and local leaders through village meetings (barazas) to sensitise community members on deworming activities.…”
Section: Discussionmentioning
confidence: 99%